A new route for enantio-sensitive structure determination by photoelectron scattering on molecules in the gas phase. Issue 43 (28th October 2022) - Fehre, Kilian; Novikovskiy, Nikolay M.; Grundmann, Sven; Kastirke, Gregor; Eckart, Sebastian; Trinter, Florian; Rist, Jonas; Hartung, Alexander; Trabert, Daniel; Janke, Christian; Pitzer, Martin; Zeller, Stefan; et al.
Abstract : Combination of Coulomb explosion imaging, molecular frame diffraction imaging, and ab initio computations provide a route for enantio-sensitive structure determination. Abstract : X-Ray as well as electron diffraction are powerful tools for structure determination of molecules. Studies on randomly oriented molecules in the gas phase address cases in which molecular crystals cannot be generated or the interaction-free molecular structure is to be addressed. Such studies usually yield partial geometrical information, such as interatomic distances. Here, we present a complementary approach, which allows obtaining insight into the structure, handedness, and even detailed geometrical features of molecules in the gas phase. Our approach combines Coulomb explosion imaging, the information that is encoded in the molecular-frame diffraction pattern of core–shell photoelectrons and ab initio computations. Using a loop-like analysis scheme, we are able to deduce specific molecular coordinates with sensitivity even to the handedness of chiral molecules and the positions of individual atoms, e.g., protons.